2010
DOI: 10.1007/s11695-010-0237-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Deficiency: A Frequent and Underestimated Complication After Bariatric Surgery

Abstract: Reduced protein intake, impaired zinc absorption and worsening compensatory mechanisms contribute to zinc deficiency. The mechanisms involved differ according to the type of surgery and time since surgery. Zinc supplementation is necessary early after bariatric surgery, but this requirement is often underestimated or is inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(53 citation statements)
references
References 61 publications
4
42
1
6
Order By: Relevance
“…We also found a decrease in selenium serum concentrations and selenium deficiency in 46 % of patients, as well as a drop in zinc serum concentrations and zinc deficiency in 15 % of patients. These values are in line with previously published selenium and zinc deficiency rates after RYGB for obese patients [22][23][24][25]. The decrease can be explained by the bypassing of the selenium resorption site in the duodenum and proximal jejunum [26].…”
Section: Discussionsupporting
confidence: 91%
“…We also found a decrease in selenium serum concentrations and selenium deficiency in 46 % of patients, as well as a drop in zinc serum concentrations and zinc deficiency in 15 % of patients. These values are in line with previously published selenium and zinc deficiency rates after RYGB for obese patients [22][23][24][25]. The decrease can be explained by the bypassing of the selenium resorption site in the duodenum and proximal jejunum [26].…”
Section: Discussionsupporting
confidence: 91%
“…A retrospective study showed that supplementation with 8 mg Zn/d was insufficient to prevent plasma zinc reductions (30). Plasma zinc concentrations ,70 lg/dL increased from 8.1% before surgery to 34.8% 24 mo after RYGBP, despite supplementation of patients with an average of 20-23 mg Zn/d (11). Thus, the available data, although limited, suggest that zinc deficiency may also be a prevalent condition in patients undergoing this type of bariatric surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of the effects of gastric bypass on other minerals, zinc for example, is very limited (10,11). Of the potential causes of zinc deficiency, a reduced zinc absorption capacity has frequently been mentioned, but the experimental evidence to support this is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners should rely on the clinical picture and laboratory data to assess the need for supplemental zinc. Oral Zinc supplement of 15-20 mg per day or up to 60 mg per day in the setting of malabsorption is advised [111].…”
Section: Nutritional Statusmentioning
confidence: 99%